2021
DOI: 10.1108/jsocm-11-2020-0221
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relevance of the traditional marketing mix across different stages of change: empirical evidence from household recycling

Abstract: Purpose This study aims to provide empirical evidence and a different perspective on the relevance of the traditional marketing mix in social marketing programmes. This is a response to the ongoing debate about the (in)compatibility of the traditional marketing mix (the 4Ps) in the field of social marketing. In doing so, this study examines the important role that the stages of behaviour change play in influencing the effectiveness of traditional marketing mix elements in the context of recycling in South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The study by Issock et al (2021) [25] showed that the impact of the marketing mix depends on the stage of change at which the target audience is. Thus, the results show that the elements of the marketing complex significantly affect the intention to act, when the target audience is in the stages of reflection and preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Issock et al (2021) [25] showed that the impact of the marketing mix depends on the stage of change at which the target audience is. Thus, the results show that the elements of the marketing complex significantly affect the intention to act, when the target audience is in the stages of reflection and preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marketing scholars have redefined the original 4P concept, expanded the 4Ps with additional Ps, and developed new concepts to supplant the marketing mix in response to widespread criticism of the marketing mix from academics and practitioners (Lahtinen et al, 2020) There are limitations in adopting the traditional marketing mix in social marketing initiatives have provided relevant arguments. This study discusses the limitations of the traditional marketing mix in behavior change programs and the need for a segmented approach based on the stages of behavior change when using the 4Ps (Issock Issock et al, 2021). The study (Cruz-Milán, 2022) identified factors that are internal and external to the company because they affect the implementation of the marketing mix.…”
Section: …………………………………………………………………………………………………………………………………… Issn : 28...mentioning
confidence: 99%
“…This process requires communication to achieve different outcomes, in parallel with the assumptions of the levels of the hierarchy of effects (Bleoju et al, 2016). Furthermore, the whole process requires different marketing techniques to reinforce the social benefit of change, minimizing barriers and ensuring accessible conditions for change (Issock Issock et al, 2021).…”
Section: Social Marketing and The Stages Of Social Changementioning
confidence: 99%
“…Although segmented social marketing interventions can follow the model of the stages of behavior change (Issock Issock et al, 2021), the campaigns tend to ignore the maintenance stage of TTM (Akdas ¸& Cismaru, 2021), thus requiring a more robust focus on retention and loyalty to achieve the desired attitudinal and behavioral changes. The incorporation of digital marketing in the social marketing strategy allows, in this sense, the use of real time digital analytics, which can be an advantage for that purpose.…”
Section: A Conceptual Model For An Omnichannel Strategy To Social Changementioning
confidence: 99%
See 1 more Smart Citation